The mad women's ball - Mas, Victoria (The Overlook Press, an imprint of Abrams, 2021)
"The Salpetriere Asylum: Paris, 1885. Dr. Charcot holds all of Paris in thrall with his displays of hypnotism on women who have been deemed mad and cast out from society. But the truth is much more complicated- these women are often simply inconvenient, unwanted wives, those who have lost something precious, wayward daughters, or girls born from adulterous relationships. For Parisian society, the highlight of the year is the Lenten ball- the Madwomen's Ball- when the great and good come to gawk at the patients of the Salpetriere dressed up in their finery for one night only. For the women themselves, it is a rare moment of hope. Genevieve is a senior nurse. After the childhood death of her sister Blandine, she shunned religion and placed her faith in both the celebrated psychiatrist Dr. Charcot and science. But everything begins to change when she meets Eugenie, the 19-year-old daughter of a bourgeois family that has locked her away in the asylum. Because Eugenie has a secret: she sees spirits. Inspired by the scandalous, banned work that all of Paris is talking about, The Book of Spirits, Eugenie is determined to escape from the asylum- and the bonds of her gender- and seek out those who will believe in her. And for that she will need Genevieve's help . . ."---Amazon.